2018
DOI: 10.1111/ffe.12894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress regime‐dependent creep behaviour on measurement of creep strain rate based on small specimen techniques

Abstract: Small specimen creep testing technique has become a hot topic of research as bulk materials are not available in many occasions. The stress distributions in the small specimens such as small punch and 3‐point bending specimens are essentially nonuniform. As it is known, the creep deformation/damage accumulation mechanisms exhibited at a high stress regime are not the same as the ones at a lower stress regime for many engineering alloys. The potential measurement errors because of stress regime‐dependent creep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…This is in good agreement with the previous numerical results on P91 steel and A7N01 aluminum alloy. 32 On the other hand, in the case of the Sinh model, the _ ε eq =_ ε u generally decreases with increasing the stress level. As a consequence, the higher the stress level, the higher the measurement error.…”
Section: Influence Of Frictionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in good agreement with the previous numerical results on P91 steel and A7N01 aluminum alloy. 32 On the other hand, in the case of the Sinh model, the _ ε eq =_ ε u generally decreases with increasing the stress level. As a consequence, the higher the stress level, the higher the measurement error.…”
Section: Influence Of Frictionmentioning
confidence: 95%
“…[29][30][31] Contrary to the uniaxial creep tension specimens, small specimens under creep conditions may exhibit complex mechanical responses, for example, SPT, thereby leading to nonuniform stress and strain fields in the specimen. 17,32,33 Accordingly, even though a constant external force is applied, different regions of the small specimen are likely to sustain simultaneously different creep deformation mechanisms due to the stress regimedependent creep behavior. In view of this, the stress regime-dependent creep behavior of materials may greatly influence the evaluation of creep properties based on SSTT.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the two-creep mechanism when simulating the crack growth rate gives a better prediction. In another study, Tu et al [11] investigated the effect of different creep mechanisms on creep behaviour and strain rate using a small specimen technique and found that the error may occur at the transition between creep mechanisms. Therefore, more attention should be given when simulating this area.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports [12][13][14][15][16][17][18][19][20][21][22][23] prove that by increasing the grain size, the creep rate will decrease or increase based on the experiment conditions, material properties, and role of the grain boundaries. For stainless steel, Lee et al 12 prove that as the grain size increases, the steadystate creep rate decreases to a minimum value and then increases from the intermediate grain size.…”
mentioning
confidence: 99%
“…[10][11][12] Thus, several studies have been conducted regarding the influence of grain size on the creep properties, and mechanical properties had been conducted on many metals such as stainless steel, copper, and Ni-based superalloys. [12][13][14][15][16][17][18][19][20][21][22][23] Surprisingly, not many researchers investigated in detail the correlation between microstructures and properties of these alloys. Therefore, this paper aims to discuss the relationship between change in the microstructure, specifically on the grain size after heat treatment, on the high-temperature creep performance of Fe-Ni-Cr alloy.…”
mentioning
confidence: 99%